If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3k = 2k + 9 Reorder the terms: 3k = 9 + 2k Solving 3k = 9 + 2k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-2k' to each side of the equation. 3k + -2k = 9 + 2k + -2k Combine like terms: 3k + -2k = 1k 1k = 9 + 2k + -2k Combine like terms: 2k + -2k = 0 1k = 9 + 0 1k = 9 Divide each side by '1'. k = 9 Simplifying k = 9
| N+3=-20+8 | | 7x/5=10 | | 225/ | | (-4)*3= | | X+2(x-3)=30 | | 3x*12=3x*2 | | 6.99x+0.55=11.94 | | 5x^2+3y^2-8=0 | | X+0.07x=50 | | 3x+16=6x+198 | | 8x-4+6x+15=14x+11 | | 20/-d=13 | | 17+d=20 | | 14+4a=a+4-8 | | x+y(4)=120 | | 1+2n=-10+5-n+4n | | J-1.2(.4-.1j)=2.88 | | 0.4x=60 | | Bx+9=3y | | 5y+20=7x-56 | | x/5-7/4=x/10-1/20 | | -6n-5n=-16-7n | | 9/22=x/176 | | Ar=3r+14 | | 34=x/64 | | 63-f=52 | | K-8=5k-k-5 | | .2I+4(.3+.2I)=2.2 | | 14x+2=9x+20 | | 0.1x+0.2x=6 | | -(12-t)+(2t-4)= | | 17*v/v=7 |